2007
DOI: 10.1007/s00404-007-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrasound fetal urinary bladder volume measurement: reliability of rotational (VOCALTM) technique using different steps of rotation

Abstract: Excellent correlations were found for both observers in the use of rotation angles of 15 degrees and 30 degrees . Since a significantly faster evaluation was obtained by using a 30 degrees rotation step it must be preferred to assess the FB volume. Our results show that the VOCAL technique, with a plane rotation of 30 degrees , can be used in a simple way to estimate fetal urine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…These findings are in agreement with those reported by Raine-Fenning et al, 9 Peixoto-Filho et al, 23 Rousian et al, 20 and Cheong et al 10 All methods were also valid, without significant differences between the volumes obtained using the multiplanar, VOCAL, and XI VOCAL (5, 10, 15, and 20 planes) methods for all 3 objects (sphere, regular cylinder, and irregular cylinder). However, all measurements performed by both examiners tended to overestimate the real volumes of the sphere and irregular cylinder on average by 2.89%.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are in agreement with those reported by Raine-Fenning et al, 9 Peixoto-Filho et al, 23 Rousian et al, 20 and Cheong et al 10 All methods were also valid, without significant differences between the volumes obtained using the multiplanar, VOCAL, and XI VOCAL (5, 10, 15, and 20 planes) methods for all 3 objects (sphere, regular cylinder, and irregular cylinder). However, all measurements performed by both examiners tended to overestimate the real volumes of the sphere and irregular cylinder on average by 2.89%.…”
Section: Discussionsupporting
confidence: 82%
“…22 Another study assessing fetal bladder volumes confirmed that VOCAL with 15° and 30°a ngles was reproducible and concordant. 23 The interval selected for the multiplanar method in this study was 5 mm. Pang et al 24 compared the accuracy of 3DUS in volumetric assessments using different numbers of planes.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D Vocal R technology has been evaluated as adequate to determine FUPR in single gestations that presented an intra-and inter-observer correlation with 15°-and 30°-rotation angles (Peixoto-Filho et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The 30°-rotation angle used in our study was based on work published by the same group that evaluated singleton pregnancies (Peixoto-Filho et al, 2007). Considering that Yamamoto et al (2007) observed that the interval between V1 and V2 acquisitions must be less than those described for single gestations, we chose an interval from 1 to 5 min to avoid capturing the urination phase in one or both.…”
Section: D Vocalmentioning
confidence: 99%
“…It has been suggested recently that serial measurements of the fetal bladder volume by 3-dimensional sonography could be used to obtain the fetal urine production rate. [18][19][20][21][22][23][24][25][26] The objective of this study was to evaluate whether fetal urine production rate measurement is useful for predicting adverse outcomes in patients with uteroplacental insufficiency.…”
mentioning
confidence: 99%